Duhamel Procedure untuk Hirschsprung’s Disease Anak di RS Syaiful Anwar Malang - Herry Wibowo (KELUWIH: Jurnal Kesehatan dan Kedokteran, 2021)
Abstract— The diagnosis of Hirschprung's disease is made with barium enema and rectal biopsy in full thickness. The Duhamel procedure was performed in 8 cases in 2008 for cases of Hirschsprung's disease. Age range of patients 7 months to 11 years. The average body weight when operated on is 7-21 kg. Morbidity and mortality after surgery were not launched. Anorectal myectomy with low anterior resection, the Duhamel-Martin procedure, and the Soave pull-through endorectal procedure are the most acceptable methods for surgical management. Hirschsprung's disease was treated in Syaiful Anwar Hospital Malang in 2008 with the following data: 1 person in January (1 year), 1 person in February (6 years), 1 person in March (7 years), 3 people in April ( 7 months, 4 years and 2 years), 2 people in August 2008 (7 months and 11 years). Enlarged abdomen with bloating, repeated constipation and sometimes aborted. Withdrawal procedures that work with endorectal withdrawal procedures, all show long results Keywords: duhamel technique, hirschsprung's disease, constipation, infant Abstrak— Diagnosis penyakit Hirschprung dibuat dengan barium enema dan full-thickness rectal biopsy. Duhamel procedure telah dilakukan pada 8 kasus pada tahun 2008 untuk kasus Hirschsprung's disease. Rentang usia penderita 7 bulan hingga 11 tahun. Berat badan rata – rata saat dioperasi 7 – 21 kg. Morbiditas dan mortalitas setelah operasi tidak dilaporkan. Anorectal myectomy dengan low anterior resection, Duhamel-Martin procedure, dan Soave endorectal pull-through procedure adalah metode yang paling dapat diterima untuk penatalaksanaan bedah. Didapatkan Kasus penyakit Hirschsprung's yang berobat di Rumah Sakit Syaiful Anwar Malang selama tahun 2008 dengan data sebagai berikut yaitu 1 orang di Januari (1 tahun) , 1 orang di Februari (6 tahun), 1 orang Maret (7 bulan), 3 orang April (7 bulan, 4 tahun dan 2 tahun), 2 orang Agustus 2008 (7 bulan dan 11 tahun). Tiap penderita mengalami riwayat abdominal distention dengan gejala perut kembung berulang, konstipasi dan kadang –kadang disertai mual. Delapan penderita yang menjalani operasi dengan prosedur endorectal pullthrough , semuanya menunjukkan hasil jangka panjang yang memuaskan. Kata kunci: tehnik duhamel, penyakit hirschsprung's , konstipasi, infant